Pasien Kanker Payudara yang Menerima Terapi Tamoxifen di Dua Rumah Sakit Swasta di Jawa Tengah: Profil Sosiodemografi, Klinis, dan Pengobatan - Setiawardani, Maria Fitri; Cholisoh, Zakky; Hapsari, Pramudita Mila (Journal of Pharmaceutical and Sciences, 2025)
Breast cancer is one of the most common types of cancer, including in Central Java Province, Indonesia, which reports a high incidence. The number of cases continues to increase, likely due to low public awareness of breast self-examination (BSE), limited health education, and a lack of motivation to undergo regular check-ups. One of the main treatment options is hormonal therapy, with Tamoxifen being the most widely used drug. To date, there is limited data on the sociodemographic and clinical characteristics among breast cancer patients who use Tamoxifen in Central Java. This information is essential for improving patient care and treatment strategies. This study aimed to describe the sociodemographic and clinical characteristics of breast cancer patients who received Tamoxifen at two private hospitals in Central Java. The results showed that most patients were under 50 years old (66%), had a low level of education (65.2%), and were employed (34.8%). Clinically, most patients were in advanced stages (56.5%), had no comorbidities (89.7%), and were not taking other medications (85%). These findings provide an initial overview of the profile of breast cancer patients using tamoxifen at two private hospitals in Central Java. However, these results cannot be generalized to the entire Central Java region due to the limitations of the study locations. Further studies with a broader scope are needed to obtain more representative data.